(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
Below in this article, an opinion is expressed about the necessary, targeted introduction of methodological innovations aimed at solving non-standard problems on the topic of mathematics “Pythagorean Theorem” among students of general secondary education, special and presidential schools.